Impact of the Oxford canal on water quality and ecological status of the River Cherwell. - Dowdeswell-Downey, Luke (Cranfield University, 2021)
Good quality water provides numerous ecosystem services and it is a legal requirement of the Water Framework Directive for all waterbodies to be achieving good status. Achieving good water quality and ecological status remains a critical issue throughout most waterbodies within the UK. Waterbodies can have an impact on one another, however, determining the impact of tributaries and canal interactions on rivers remains a challenge. This study aims to investigate whether the Oxford canal has had a negative impact upon water quality and ecological status of the River Cherwell. New water quality and sediment samples were collected, upstream and downstream of where the river and canal interact at two sections at 16 sampling locations. Historical invertebrate data was examined at three locations; upstream, between and downstream of these two sections along the River Cherwell and compared to the nearby River Windrush, which does not interact with any canals. Results showed no statistical decreases in river water quality downstream of where the canal joins the river. Conversely, there was evidence that interaction with the canal water may have decreased river nutrient levels, such as nitrate, by a dilution effect. Furthermore, mixing with river water may have significantly increased orthophosphate and conductivity in the canal (p< 0.05). Similarly, invertebrate data showed no negative impact from the canal on the river in terms of taxa richness, BMWP, ASPT, and diversity indices. However, results suggested that the River Cherwell has had higher invertebrate metrics and indices when compared to the River Windrush. Overall, this study found no evidence to indicate that the Oxford canal negatively impacted water quality and ecological status of the River Cherwell.
Keywords: Nitrate; phosphorus; invertebrate; historical data; control-impact; dilution